(untitled) (Nomico, 2026)
Labor productivity is a key determinant of economic competitiveness and sustainable growth, yet Indonesia continues to face structural challenges in its formal labor market. Minimum wage policy is frequently used to improve worker welfare, but its impact on productivity remains debated, particularly in relation to job insecurity. This study aims to analyze the effects of minimum wage and job insecurity on labor productivity in Indonesia’s formal sector. Using a quantitative explanatory design, the research combines secondary provincial data on minimum wages and productivity indicators with primary survey data measuring perceived job insecurity among formal sector workers. Multiple linear regression analysis, including an interaction term, is employed to examine direct and moderating effects. The findings indicate that minimum wage has a positive and significant effect on labor productivity, while job insecurity negatively affects productivity. Moreover, job insecurity weakens the positive relationship between minimum wage and productivity. The study concludes that minimum wage can either promote or constrain productivity depending on employment stability and enforcement conditions. Effective wage policy must therefore be accompanied by strengthened job security and institutional support to ensure sustainable productivity growth